Pengaruh Kegiatan Eksplorasi Bahan Alam terhadap Kreativitas Anak Usia Dini TK Jambu Putih - Evi Muliana A. Nduling; Elva M. Sumirat; Jilda H. Sausambu; Kezia Toikene; Madinatul Munawara Sideng (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Creativity is one of the essential developmental aspects that needs to be stimulated from an early age through meaningful and experience-based learning activities. This study aims to measure the effect of natural material exploration activities on the creativity of early childhood at TK Jambu Putih, Boyomoute Village. This research employed a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The research subjects consisted of 30 children aged 4–6 years divided into an experimental group (n=15) and a control group (n=15) using total sampling technique. The research instrument was a creativity observation sheet developed based on Guilford's four indicators, namely fluency, flexibility, originality, and elaboration, with a 1–4 rating scale. The treatment was carried out over 8 sessions in 4 weeks using various natural materials available in the school's surrounding environment. Data were analyzed using independent ttest after fulfilling the prerequisite tests of normality and homogeneity. The results showed that the mean post-test score of the experimental group (82.67) was significantly higher than that of the control group (68.40), with tvalue = 6.842 and significance of 0.000 (p < 0.05). Therefore, natural material exploration activities are proven to have a positive and significant effect on the creativity of early childhood. These findings confirm that naturebased media is an effective, economical, and contextual learning strategy in developing early childhood creativity.